Insights into shape of uveal melanoma: a comprehensive evaluation of clinical features, pathological features, and prognosis analysis - Lou, Heng; Yue, Han; Qian, Jiang; Bi, Yingwen; Lin, Xintong; Chen, Haifeng; Xu, Binbin; Ma, Ruiqi; Xue, Kang; Guo, Jie (Frontiers in Medicine, 2025)
BackgroundMany patients with uveal melanoma (UM) cannot receive laboratory analysis due to eye-preserving treatment, biopsy risks or costs. The study is to evaluate correlation between tumor shape and a series of metastasis risks in UM, and to assess the predictive value of tumor shape classification.MethodsFour hundred thirty-nine UM patients undergoing enucleation were included in the study. Standardized echography was utilized to document selected tumor characteristics. Tumors were categorized into five distinct shape groups: mushroom, dome, lobulated, diffuse, and irregular. Clinical data, tumor thickness, largest basal diameter (LBD), American Joint Committee on Cancer (AJCC) stage, pathological results, and survival status were collected and comparatively analyzed across the different tumor shapes. Survival analysis was carried out with both Cox hazard regression and Kaplan–Meier log rank test.ResultsThe 439 UM cases were classified as mushroom in 164 (37.4%), dome in 129 (29.4%), lobulated in 62 (14.1%), diffuse in 11 (2.5%) and irregular in 73 (16.6%). Significant differences were observed in tumor thickness, LBD, cell type, ciliary body involvement (CBI), extraocular extension, and AJCC stage across these shape categories. Regardless of tumor size and AJCC stage, mushroom-shaped melanoma exhibited the most favorable prognosis, irregular-shaped melanoma demonstrated the worst prognosis.ConclusionTumor shape could be defined noninvasively and dependably using echography. Shape classification in UM provides an independent variable to improve the clinical prognostication.